2022
DOI: 10.1186/s12877-022-02816-y
|View full text |Cite
|
Sign up to set email alerts
|

Obstacles to access to community care in urban senior-only households: a qualitative study

Abstract: Background The increased number of older adults living alone has created a substantial care need. However, the utilization rate of services and facilities to meet these needs are surprisingly low. Many of older adults experience difficulties accessing these services, although it remains unclear how these obstacles impede access to services. This study explored the obstacles and difficulties experienced by urban older adults in seeking community care. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 59 publications
(40 reference statements)
1
15
0
Order By: Relevance
“…Poor SRH was also 6.20 times higher in older women with restrictions in daily functions than those without restrictions in daily functions. A study reported that more restrictions on daily activities were associated with poor SRH in older people in Korea, which is partially supported by the results of this study [ 15 ]. In a study that analyzed the functional impairment of older people living alone based on the 2017 National Survey of Older Koreans [ 4 ], it was reported that restrictions in daily functioning that interfered with the independent performance of the ADL negatively affected the SRH of older women living alone.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Poor SRH was also 6.20 times higher in older women with restrictions in daily functions than those without restrictions in daily functions. A study reported that more restrictions on daily activities were associated with poor SRH in older people in Korea, which is partially supported by the results of this study [ 15 ]. In a study that analyzed the functional impairment of older people living alone based on the 2017 National Survey of Older Koreans [ 4 ], it was reported that restrictions in daily functioning that interfered with the independent performance of the ADL negatively affected the SRH of older women living alone.…”
Section: Discussionsupporting
confidence: 85%
“…Choi and Lee [ 19 ] reported that the level of education strongly affected the health of older people: the lower the education level, such as elementary school graduation or below, the higher the inequality in SRH. The higher the education level, the more social resources are accessible and utilized, such as health information and medical service use networks; thus, a more positive self-assessment of older people’s health was reported in participants with a high level of education [ 15 ]. Conversely, poor SRH was reported among participants with a low level of education who lack support systems, such as family members, as they experience difficulty in acquiring and internalizing health information.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although older people are the main consumers of healthcare services, stereotypes, prejudice, discrimination, and structural obstacles such as inconvenient transportation, shortage of geriatric specialists, and the spread of digital healthcare make it difficult for older people to access relevant resources [19,20]. Our research team conducted a qualitative study to reconstructed the paths and obstacles encountered by older adults in seeking community care services, and found multiple barriers, which were lack of community care information, limited mobility, complex process of achieving care, and incomprehension of needs expression, deterred the access of care resources for older adults effectively [21]. The quality of community care services may need to be improved, as service providers tend to provide care in the most convenient way, which may not be suitable for older adults [22].…”
Section: Introductionmentioning
confidence: 99%
“…These fragmented experiences do not allow for a comprehensive and in‐depth understanding of the need for volunteer services among the home‐based elderly. Furthermore, compared to rural areas, elderly people living in cities have a more difficult life and can easily become disconnected from society 31 . As a result, it is necessary to investigate the experience and expectations of urban home‐based older adults receiving volunteer service to point out the direction for volunteers to provide assistance services tailored to their needs.…”
Section: Introductionmentioning
confidence: 99%